2021
DOI: 10.1177/10776990211008534
|View full text |Cite
|
Sign up to set email alerts
|

Schadenfreude After Watching the News: How Audiences Respond to Media Coverage of Partisans Disclosing Illnesses

Abstract: When public figures make announcements about their illness, audiences may be influenced to change their own health behaviors. However, if a disliked political figure becomes ill, feelings of schadenfreude, or pleasure at another’s misfortune, may arise and schadenfreude could predict news consumer’s information seeking and health-related intentions. Surveys of audience responses to news of conservative radio host Rush Limbaugh’s lung cancer diagnosis ( N = 414) and to news of Republican Senator Rand Paul’s COV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 60 publications
0
12
0
Order By: Relevance
“…For example, research shows that some people experienced schadenfreude (i.e., pleasure over another’s misery), such as when disliked dissenters contracted COVID-19 (Myrick & Chen, 2021) or those spurning the vaccine passed away (Baker-Jordan, 2021). Contempt for others based on a judgment of their immoral actions is a known predictor of schadenfreude (Berndsen & Tiggemann, 2020), and feeling schadenfreude predicts decreased willingness to engage in prevention behaviors, including COVID-19 prevention (Myrick & Chen, 2021). As such, future work may examine the potential interplay of schadenfreude and stigma associated with following (or not) public health recommendations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, research shows that some people experienced schadenfreude (i.e., pleasure over another’s misery), such as when disliked dissenters contracted COVID-19 (Myrick & Chen, 2021) or those spurning the vaccine passed away (Baker-Jordan, 2021). Contempt for others based on a judgment of their immoral actions is a known predictor of schadenfreude (Berndsen & Tiggemann, 2020), and feeling schadenfreude predicts decreased willingness to engage in prevention behaviors, including COVID-19 prevention (Myrick & Chen, 2021). As such, future work may examine the potential interplay of schadenfreude and stigma associated with following (or not) public health recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…While we expect the model to generalize to emerging stigmas on other health conditions, it is possible that COVID-19 may have unique features that exacerbated the strength of stable relationships or the fluctuations noted over time. For example, research shows that some people experienced schadenfreude (i.e., pleasure over another's misery), such as when disliked dissenters contracted COVID-19 (Myrick & Chen, 2021) or those spurning the vaccine passed away (Baker-Jordan, 2021). Contempt for others based on a judgment of their immoral actions is a known predictor of schadenfreude (Berndsen & Tiggemann, 2020), and feeling schadenfreude predicts decreased willingness to engage in prevention behaviors, including COVID-19 prevention (Myrick & Chen, 2021).…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…State Schadenfreude . We used the state Schadenfreude scale (Myrick & Chen, 2022) to assess the pleasure participants experienced from the misfortune of the person described in the scenario. This is a four‐item questionnaire that has participants rate their agreement with the items (amused, satisfied, pleased, and sympathetic) on a 1 ( strongly disagree ) to 7 ( strongly agree ) rating scale regarding how they felt about the story that accompanied their randomly assigned stimuli.…”
Section: Methodsmentioning
confidence: 99%
“…Only one published study addressed Schadenfreude related to COVID‐19. Myrick and Chen (20) had participants complete positive and negative evaluations of US Senator Rand Paul (known for his stance against mandatory public health measures such as vaccinations) before reading a news report about him getting COVID‐19, and then participants completed a measure of Schadenfreude. Results showed that both positive and negative evaluations of Rand Paul positively predicted Schadenfreude.…”
Section: Schadenfreudementioning
confidence: 99%
“…The Tall Poppy Scale was shown to predict interest in online achievement‐related information (Phillips et al, 2021 ). Similarly, the Schadenfreude associated with a disliked political figure's illness has been found to influence information seeking and health behavior (Myrick & Chen, 2022 ). Others have found that Schadenfreude contributed to the spreading of negative news online (Hornik et al, 2021a ; Hornik et al, 2021b ; Hornik et al, 2015 ; Hornik et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%